Energy Efficient Graphene Based High Performance Capacitors - Bae, Joonwon; Seok Kwon, Oh; Lee, Chang-Soo (Recent Patents on Nanotechnology, 2017)
Background: Graphene (GRP) is an interesting class of nano-structured electronic materials for various cutting-edge applications. Objective: To date, extensive research activities have been performed on the investigation of diverse properties of GRP. The incorporation of this elegant material can be very lucrative in terms of practical applications in energy storage/conversion systems. Method: Among various those systems, high performance electrochemical capacitors (ECs) have become popular due to the recent need for energy efficient and portable devices. Therefore, in this article, the application of GRP for capacitors is described succinctly. In particular, a concise summary on the previous research activities regarding GRP based capacitors is also covered extensively. Result: It was revealed that a lot of secondary materials such as polymers and metal oxides have been introduced to improve the performance. Also, diverse devices have been combined with capacitors for better use. Conclusion: More importantly, recent patents related to the preparation and application of GRP based capacitors are also introduced briefly. This article can provide essential information for future study
Keywords: graphene